Model Pendidikan Agama dalam Keluarga Muslim di Desa Pulutan Kecamatan Sidorejo Kota Salatiga - Rohman, Taufiqur (Edudeena : Journal of Islamic Religious Education, 2018)
Abstract: This research talk about educational model religion in the family muslim in the village pulutan kecamatan sidorejo salatiga city. Of the study focus of the research is that which is becoming problems it was islamic education in the family muslim in the village pulutan kecamatan sidorejo salatiga city and how their model religious education in the family muslim in the village pulutan kecamatan sidorejo salatiga city. This study adopted qualitative approaches , so the presence of researchers in the field very important considering researchers act directly as an instrument direct and a gatherer data from the observation deep and actively involved in research .The data shaped words taken from informants and respondents when they were interviewed .In other words the data clear signs from informants , data on supplementary documents .A whole the data besides the interviews obtained from observation and documentation .Data analysis done by means of review existing data , and held reduction data , presentation of data , draw conclusions and the final stages of data analysis this is have something of the validity of data. Of its reserach obtained the results of research as follows: problems it was religious education in muslim families in the village pulutan subdistrict sidorejo salatiga city caused by several factors, that is lack of attention of parents and exemplary factors of parent and child that is less interest in studying islam . Educational model religion in the family muslim in the village pulutan kecamatan sidorejo salatiga 2015 city said it would follow the democratic authoritarian and models.   Abstrak: Penelitian ini membahas tentang Model Pendidikan Agama dalam keluarga muslim di Desa Pulutan Kecamatan Sidorejo Kota Salatiga. Fokus yang dikaji dalam penelitian ini adalah apa yang menjadi problematika pendidikan Islam dalam keluarga muslim di Desa Pulutan Kecamatan Sidorejo Kota Salatiga dan bagaimana Model pendidikan agama dalam keluarga muslim di Desa Pulutan Kecamatan Sidorejo Kota Salatiga. Penelitian ini menggunakan pendekatan kualitatif, jadi kehadiran peneliti di lapangan sangat penting sekali mengingat peneliti bertindak langsung sebagai instrumen langsung dan sebagai pengumpul data dari hasil observasi yang mendalam serta terlibat aktif dalam penelitian. Data yang berbentuk kata-kata diambil dari para informan/ responden pada waktu mereka diwawancarai. Dengan kata lain data-data tersebut berupa keterangan dari para informan, sedangkan data tambahan berupa dokumen. Keseluruhan data tersebut selain wawancara diperoleh dari observasi dan dokumentasi. Analisa data dilakukan dengan cara menelaah data yang ada, lalu mengadakan reduksi data, penyajian data, menarik kesimpulan dan tahap akhir dari analisa data ini adalah mengadakan keabsahan data. Dari penelitian yang dilaksanakan diperoleh hasil penelitian sebagai berikut: Problematika Pendidikan Agama dalam Kelurga Muslim di Desa Pulutan Kecamatan Sidorejo Kota Salatiga disebabkan oleh beberapa faktor, yaitu faktor kurangnya perhatian dari orang tua dan faktor keteladanan dari orang tua serta minat anak yang kurang dalam mempelajari agama Islam. Model Pendidikan Agama dalam keluarga muslim di Desa Pulutan Kecamatan Sidorejo Kota Salatiga tahun 2015 menggunakan model otoriter dan model demokratis